Pengaruh Modal Usaha Dan Biaya Sewa Tempat Usaha Terhadap Pendapatan Pedagang Pasca Relokasi : Studi Kasus di Pasar Pelita Kota Sukabumi - Pujianti, Vinni; Idang Nurodin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Abstract. This study aims to determine the effect of Business Capital variables and Business Place Rental Fees on Post-Relocation Merchants' Income at Pelita Market, Sukabumi City. The method used in this research is quantitative research using primary data. The variables used in this study are Business Capital and Business Rental Costs as independent variables and Merchant Income as the dependent variable. The population in this study were 288 Los traders in Pelita Market, Sukabumi City. Sampling technique with Probability Sampling technique with simple random sampling method. Probability sampling nonprobability sampling with a total of 76 people. The results of research using SPSS 27 for Windows software show that partially business capital has a significant positive effect on trader income where t count> t table (2.047> 1.666) with a significant value of 0.044 < 0.05. The cost of renting a business place shows a partially significant positive effect on the income of traders where t count> t table (2.493> 1.666) with a significant value of 0.015 <0.05. The results of simultaneous testing in this study indicate that business capital and business premises rental costs affect the income of traders in Pelita Market, Sukabumi City by 22,2% while the rest is influenced by other factors not examined by researchers.